2005
DOI: 10.1590/s1677-55382005000200003
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal shock wave lithotripsy in the treatment of renal pelvicalyceal stones in morbidly obese patients

Abstract: We conclude that ESWL with the Siemens Lithostar-plus is the most effective and cost-efficient in morbidly obese patients with pelvic stones sized between 6 and 20 mm. 87% success rate was achieved. The increased distance from the skin surface to the stone in those patients does not decrease the success rate provided the stone is positioned in the focal point or within 3 cm of it on the extended shock pathway. ESWL should not be considered as the first line of treatment in the morbidly obese patients with low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 10 publications
1
18
0
1
Order By: Relevance
“…In recent years, it has been suggested that central obesity might play an important role in the success rate of SWL [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, it has been suggested that central obesity might play an important role in the success rate of SWL [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, ESWL plays an important role in the treatment of nephrolithiasis in obese patients, since it is a safe procedure without the need for anesthesia [11,21]. However, the ESWL efficacy in obese patients is not as high as in non-overweight patients, mainly due to poorer identification of the stone, increased skin-to-stone distance and the shock-wave attenuation by body fat, which has some effect on the efficiency of stone fragmentation [7,11,17,19,21].…”
Section: Discussionmentioning
confidence: 99%
“…However, the ESWL efficacy in obese patients is not as high as in non-overweight patients, mainly due to poorer identification of the stone, increased skin-to-stone distance and the shock-wave attenuation by body fat, which has some effect on the efficiency of stone fragmentation [7,11,17,19,21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the intracorporeal portion of distance to the focal point increases, stone fragmentation and clearance is reduced. Other important drawback is that other variables that have been related to outcome, such as stone location and composition (9,10), and data obtained from a NCCT such as radiographic density measured in Hounsfield Units (HU) (11-13), anatomical findings and SSD (4,14) were not included in the analysis. A special consideration should be made regarding SSD, a test addresses the same issue as the Lithotripsy table height.…”
Section: Discussionmentioning
confidence: 99%